Towards the development of fiber lasers for the 2 to 4 nanom spectral region - Fortin, Vincent; Bernier, Martin; Caron, Nicolas; Faucher, Dominic; El Amraoui, Mohammed; Messaddeq, Younes [UNESP]; Vallée, Réal (SPIE, the international society for optics and photonics, 2013)
A growing number of applications are calling for compact laser sources operating in the mid-infrared spectral region. A review of our recent work on monolithic fiber lasers (FL) based either on the use of rare-earth fluoride fibers or on Raman gain in both fluoride and chalcogenide glass fibers is presented. Accordingly, an erbium-doped double clad fluoride glass all-FL operating in the vicinity of 3 μm is shown. In addition, we present recent results on the first demonstrations of both fluoride and chalcogenide Raman fiber lasers operating at 2.23 and 3.34 μm, respectively. It is shown that based on this approach, monolithic FLs could be developed to cover the whole 2 to 4 μm spectral band.